Mathematical model based on genetic algorithms to optimize profits in an underground passenger transport company (SCIÉNDO INGENIUM, 2023)
The main objective of this research was to improve profits in an interprovincial passenger transport company, having designed a mathematical programming model and a genetic algorithm model with the purpose of reaching solutions for a future optimization of the company's profits. The type of research was applied, the technique that was applied was the survey and the sample was made up of all the variables of income, costs and profits of an interprovincial passenger transport company in the Peruvian territory. The results confirmed that the implementation of a mathematical model based on genetic algorithms contributes significantly to the optimization of profits, since the profit associated with the economic bus was improved, to the sleeper bus, to the mixed bus and to the super sleeper bus, achieving an optimal occupancy rate of 58.33%, 85.00%, 58.33% and 95.00%, respectively. The implemented model was based on a chromosome size of 19 bits, the population size was 10 chromosomes, the selection method is probabilistic with 4 chromosomes, crossing with four chromosomes, type of multipoint crossing and mutation process a from the second iteration of probabilistic type.
Keywords: genetic algorithm; chromosome; utility; transport companies